Pesticide exposure, health impacts, predeterminism, and health insurance demand among Pakistani farmers: Implications for policy - Muhammad Arshad; Yasir Mehmood; Aravindakshan, Sreejith; Ullah, Ayat; Sieber, Stefan; Krupnik, Timothy Joseph (Elsevier, 2025)
The indiscriminate use of chemical pesticides, regardless of pest infestation, is widespread in the developing world to mitigate agricultural losses. Farmers face significant health risks from pesticides, yet indemnity provision is often neglected in policy discussions. Socio-cultural factors, including religion and trust in governments, can influence indemnity demand, especially among religious communities. However, little to no attention has been given to religious predeterminism and public trust in indemnity service design. We employed a novel approach integrating count data models with contingent valuation to analyze the health impacts of pesticide use and influence of socioeconomic factors, particularly religious predeterminism and public trust, on health insurance demand among farmers in rural Pakistan. Results reveal critical health risks posed by pesticide use among farmers and highlight the limited willingness to pay for health insurance to mitigate these risks. Findings from the Negative Binomial (NB) regression model showed significant positive effects of pesticide quantity (β = 0.607, p < 0.05), WHO Class IA-and-IB pesticides (β = 0.420, p < 0.05), and WHO Class II pesticides (β = 0.277, p < 0.05) on farmers' health. Religious predeterminism and public trust significantly influence farmers' willingness to pay, with only about 27 % of farmers expressing readiness to pay an average of US$4.02 per annum for health insurance. These findings emphasize the importance of tailored health insurance designs that accommodate religious beliefs. Policy initiatives should focus on educating farmers about safe pesticide use and health insurance benefits. Governments can build public trust through subsidized insurance schemes to reduce farmers' out-of-pocket health expenses. The findings emphasize the role of socio-cultural factors, in shaping insurance uptake, suggesting that health insurance policies must be tailored to align with farmers’ belief systems. Government-led initiatives, including subsidized insurance schemes, are essential to enhance public trust, foster safe farming practices, and support sustainable agriculture.